The system of the key indicators of formation of attractive investment climate of Ukraine and peculiarities of their management - Корбутяк, Аліна Георгіївна (LLC “Consulting Publishing Company “Business Perspectives”, 2020)
Ukraine, as a young country, is creating the investment market, which is the most important component of the national economy under the challenges and threats of the XXI century, instability and hybrid war. The study aims to analyze the investment climate and investment attractiveness of Ukraine and to identify key indicators through the political, legal, economic, social, and other conditions under which its investment market will become attractive. The dynamics investigation of foreign direct investments (FDI) inflows into Ukraine during 2002–2018, their structural analysis enabled to identify the periods of the most significant fluctuations and to state the reasons for such changes, to differentiate priority sectors of the Ukrainian economy being of financial interest to foreign investors, which is as a whole the basis of the attractive investment climate formation and management in the country. The methods of financial management system, including the method of SWOT analysis, were applied to determine investment weaknesses, threats, strengths and opportunities, considering the peculiarities of their management. As a consequence of the analysis on the reasons for the reduction of foreign investments in the country economy, it is proved that the proposed mechanism for improving the investment climate in the country will allow increasing FDI inflows and financing the general capital investments.
Problems and Perspectives in Management
Keywords: attractiveness, factors, investment, management, problems, SWOT analysis